(Re)organizing the music curriculum as multicultural music education. (November 2021) - de Villiers, Alethea Cassandra
Cultural hegemony permeates society and is spread through social institutions. These institutions socialize people into the norms, values and beliefs of the dominant social groups. Moreover, cultural hegemony is spread and perpetuated through education in the form of compulsory education, a national curriculum, national assessments, as well as the hidden curriculum. The cultural hegemony of Western Art Music is established as the standard of music making and is institutionalized in education systems, national curricula and national assessment practices because it is inherent in ideologies and decision making. To counter the dominant hegemony, multicultural education philosophies have been adopted in democracies. The purpose of multicultural education is to change the dominant hegemony and bring about transformation in policy, attitudes, curriculum, assessment, the language of instruction, and strategies for learning and teaching. In this article, I discuss and compare music curricula from South Africa and Australia to determine how multiculturalism is manifested in the curriculum content for music in schools. I also suggest possible frameworks for curriculum developers in democracies to consider, which would subvert the status quo and establish a counter-hegemony.